2009
DOI: 10.1080/00223890902935738
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the White Bear Suppression Inventory (WBSI): A Review of Previous Findings and a New Approach

Abstract: The White Bear Suppression Inventory (WBSI; Wegner & Zanakos, 1994) was originally designed to assess people's inclination toward thought suppression. In this article, we provide a detailed review of previous findings on the structure of this instrument and present a study that took a new statistical approach. It involved an exploratory factor analysis of the French WBSI using the weighted least squares mean and variance estimator as well as parametric item response theory analyses. Results clearly supported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 29 publications
3
48
0
7
Order By: Relevance
“…Finally, because it has been argued that the WBSI measures the tendency to have intrusive thoughts as well as the tendency to try to supress thoughts, correlations were further performed on the data with a 'Suppression' subscale and an 'Intrusion' subscale, using items that have loaded onto each of these scales respectively across several studies (Schmidt et al, 2009). …”
Section: Correlations Between Dream Content Variables and Personalitymentioning
confidence: 99%
“…Finally, because it has been argued that the WBSI measures the tendency to have intrusive thoughts as well as the tendency to try to supress thoughts, correlations were further performed on the data with a 'Suppression' subscale and an 'Intrusion' subscale, using items that have loaded onto each of these scales respectively across several studies (Schmidt et al, 2009). …”
Section: Correlations Between Dream Content Variables and Personalitymentioning
confidence: 99%
“…Items were rated on a 7-point scale ranging from 1 (disagree strongly) to 7 (agree strongly). Recent investigations into the psychometric properties of the WBSI (Schmidt et al, 2009) have shown that it contains a 9-item subscale measuring the wish to suppress unwanted thoughts (e.g., "There are things I prefer not to think about"). In the present study, this subscale had an alpha coefficient of .86.…”
Section: The White Bear Suppression Inventory (Wbsi) -mentioning
confidence: 99%
“…In contrast, a scale for health-care professionals should be general enough to assess coping style in general (i.e., the whole set of strategies used). Second, some instruments only cover some strategies, such as emotion-focused strategies in their work 11,12) . Third, health-care professionals will certainly use some specific problem-focused strategies (e.g., presenting excuses to a patient).…”
mentioning
confidence: 99%
“…Construct validity was assessed using measures of health-care professionals' quality of life (including job and life satisfaction, and self-reported health) as well as sleep problems and depression. Results: Based on factor analysis and item response analysis, the initial 31-item scale was shortened to 15 items, which measured three types of strategies: problem-focused strategies (i.e., trying to find solutions, talking to colleagues) and two accepting one's limits 11,12) are good examples of these strategies. Seeking social support is considered either problem or emotion focused depending on its goal.…”
mentioning
confidence: 99%